Is There Life after the Complete Loss of Analyst Coverage? - Mola, Simona; Rau, P. Raghavendra; Khorana, Ajay (The Accounting Review, 2013)
ABSTRACT This paper examines the value of sell-side analysts to covered firms by documenting the effects on firm performance and investor interest after a complete loss of analyst coverage for periods of at least one year. We find that analyst coverage adds value to a firm both because it reduces information asymmetries about the firm's future performance and because it maintains investor recognition for that firm's stock. After the introduction of regulations that curtailed the informational advantage of analysts in the early 2000s, the investor recognition role of analysts remains important. Firms that lose all analyst coverage continue to suffer a significant deterioration in bid-ask spreads, trading volumes, and institutional presence but do not show a significant difference in subsequent performance relative to covered peers. In addition, controlling for other factors, we find that firms that lose all analyst coverage for one year are significantly more likely to delist than their covered peers. Our results provide insight into the reasons why firms place so much importance on analyst coverage.